A Note on Solvability of the Nonlinear Abstract Viscoelastic Problem in Banach Spaces - Andrade, D. (Trends in Computational and Applied Mathematics, 2000)
In this work we are concerned with the existence of integral solution for a nonlinear abstract viscoelastic problem in a Banach space where the operator is accretive and time dependent.